Cognitive dysfunction in Moyamoya disease: latest developments and future directions - Wang, Xilong; Liu, Ziqi; Zhou, Zhenyu; Zhang, Junze; Wang, Yanru; He, Shihao; Wang, Rong (Frontiers in Human Neuroscience, 2024)
Cognitive dysfunction is common in Moyamoya disease (MMD). However, current knowledge of cognitive impairment in MMD is inadequate. In this review, we explored the characteristics of altered cognitive function associated with MMD and offered recommendations aimed at guiding potential research endeavors into the cognitive dysfunction in MMD. Cognitive functions, including executive function, intelligence, memory and so on, show characteristic declines in MMD. The effects of cerebral revascularization surgery on cognitive impairment are controversial. Currently, there is still a lack of relevant research on cognitive impairment. Research on the pathogenesis and etiology associated with Moyamoya disease as well as long-term cohort studies, are important future directions.